Pengaruh Metode Eksperimen Berbasis Literasi Sains Terhadap Hasil Belajar IPA Pada Siswa Kelas V SD Negeri Lemoa Kecamatan Bontolempangan Kabupaten Gowa - Abrina Maulidnawati Jumrah (STKIP Andi Matappa Pangkep, 2021)
This study aims to determine the effect of scientific literacy-based experimental methods on science learning outcomes in fifth grade students of SD Negeri Lemoa, Gowa Regency. This type of research is an experimental study in the form of One Group Pretest Postest Design, which is an experiment which in its implementation only involves one class as an experimental class without a comparison class (control class) which aims to determine the effect of the experimental method in Natural Science learning. The subject of the relationship between living things in the ecosystem in grade V SD Negeri Lemoa for the academic year 2020/2021 The results of descriptive statistical analysis of science learning outcomes in fifth grade students with the experimental method based on positive scientific literacy, the understanding of material from natural science with the experimental method based on scientific literacy shows better learning outcomes than before using the experimental method. The inferential results obtained are 0.000 <0.05 so that H0 is rejected and H1 is accepted, which means that there is an effect of using scientific literacy-based experimental methods on science learning outcomes in fifth grade students of SD Negeri Lemoa, Gowa Regency.